2016
DOI: 10.1097/igc.0000000000000848
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Tissue Factor in Epithelial Ovarian Carcinoma Is Involved in the Development of Venous Thromboembolism

Abstract: ObjectivesOur 2007 study of 32 patients with ovarian cancer reported the possible involvement of tissue factor (TF) in the development of venous thromboembolism (VTE) before treatment, especially in clear cell carcinoma (CCC). This follow-up study further investigated this possibility in a larger cohort.MethodsWe investigated the intensity of TF expression (ITFE) and other variables for associations with VTE using univariate and multivariate analyses in 128 patients with epithelial ovarian cancer initially tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 19 publications
0
21
0
3
Order By: Relevance
“…In patients who have developed asymptomatic VTE prior to treatment, iatrogenic symptomatic PE may be induced intraoperatively or postoperatively when prolonged or highly invasive surgery is performed, or when intermittent pneumatic compression is applied to patients without being aware of the presence of VTE. Factors involved in the occurrence of VTE in cancer patients before treatment include: congenital predisposition to thrombophilia, vein displacement caused by the tumor and hemoconcentration due to ascites production, as well as the potential activation of the extrinsic coagulation pathway by tumor‐produced tissue factor (TF) in ovarian cancer, as shown previously by our group . It has been reported that the pre‐treatment prevalence of VTE in patients with gynecological malignant tumors is 2.8–4.8% in cervical cancer, 5.1–9.9% in endometrial cancer and 7.1–26.7% in ovarian cancer, indicating that asymptomatic cases are common.…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…In patients who have developed asymptomatic VTE prior to treatment, iatrogenic symptomatic PE may be induced intraoperatively or postoperatively when prolonged or highly invasive surgery is performed, or when intermittent pneumatic compression is applied to patients without being aware of the presence of VTE. Factors involved in the occurrence of VTE in cancer patients before treatment include: congenital predisposition to thrombophilia, vein displacement caused by the tumor and hemoconcentration due to ascites production, as well as the potential activation of the extrinsic coagulation pathway by tumor‐produced tissue factor (TF) in ovarian cancer, as shown previously by our group . It has been reported that the pre‐treatment prevalence of VTE in patients with gynecological malignant tumors is 2.8–4.8% in cervical cancer, 5.1–9.9% in endometrial cancer and 7.1–26.7% in ovarian cancer, indicating that asymptomatic cases are common.…”
Section: Introductionmentioning
confidence: 54%
“…Massive ascites was also likely identified due to hemoconcentration caused by intravascular dehydration, in addition to the direct compression applied to veins by the ascites. Clear cell carcinoma was identified as an independent and significant risk factor, possibly because clear cell carcinoma has significantly higher TF expression compared to other histological types, indicating that the extrinsic coagulation pathway may be accelerated. Additionally, stage III/IV advanced cancer, LN enlargement that suggests metastasis and tumor extension beyond the primary organ were identified as independent and significant risk factors for pretreatment VTE, and this may be a consequence of augmentation in blood coagulation through basement membrane destruction and interstitial infiltration caused by tumor extension/metastasis and stimulation from and the immune response to intravascular/intraductal entry .…”
Section: Discussionmentioning
confidence: 99%
“…Recent study demonstrated that TF was involved in the pretreatment development of VTE in ovarian cancer, particularly in CCC. [ 19 ]…”
Section: Discussionmentioning
confidence: 99%
“…В частности, известно, что при онкологических заболеваниях TF задействован в росте, неоваскуляризации и метастазировании злокачественных опухолей [11]. Кроме этого, существует большое количество экспериментальных данных, подтверждающих, что TF играет роль в развитии тромбозов (в частности, венозной тромбоэмболии (ВТ) и тромбоза глубоких вен (ТГВ)) у пациентов с онкологическими заболеваниями [12,13].…”
Section: O N C O H E M a T O L O G Y 2 ' 2 0 1 9 V O L 14unclassified
“…тканевый фактор и нарушения системы гемостаза. Как показали результаты иммуногистохимических исследований, для пациентов с карциномой яичников [13] риск развития ВТ / ТГВ выше в случае высокой экспрессии TF опухолевыми клетками.…”
Section: фундаментальные исследования в практической медицине на соврunclassified